2021
DOI: 10.1186/s13024-021-00472-1
|View full text |Cite
|
Sign up to set email alerts
|

Processing of progranulin into granulins involves multiple lysosomal proteases and is affected in frontotemporal lobar degeneration

Abstract: Background Progranulin loss-of-function mutations are linked to frontotemporal lobar degeneration with TDP-43 positive inclusions (FTLD-TDP-Pgrn). Progranulin (PGRN) is an intracellular and secreted pro-protein that is proteolytically cleaved into individual granulin peptides, which are increasingly thought to contribute to FTLD-TDP-Pgrn disease pathophysiology. Intracellular PGRN is processed into granulins in the endo-lysosomal compartments. Therefore, to better understand the conversion of i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 52 publications
3
25
0
Order By: Relevance
“…We found that several lysosomal enzymes were upregulated both in the mouse and human dataset, notably cathepsins. We showed decreased cathepsin B activity in live neurons, a phenomenon only shown in in vitro assays before 52,[54][55][56] . Similar perturbations of lysosomal acidification have been reported in non-neuron cells and other neurodegenerative diseases 57,58 .…”
Section: Discussionmentioning
confidence: 66%
“…We found that several lysosomal enzymes were upregulated both in the mouse and human dataset, notably cathepsins. We showed decreased cathepsin B activity in live neurons, a phenomenon only shown in in vitro assays before 52,[54][55][56] . Similar perturbations of lysosomal acidification have been reported in non-neuron cells and other neurodegenerative diseases 57,58 .…”
Section: Discussionmentioning
confidence: 66%
“…These gene signatures were largely specific for tauopathy; however, we identified a number of lysosomal genes that were altered in iPSC-neurons from MAPT mutations and in brains from GRN mutation carriers. GRN has been implicated in lysosomal function and neuronal integrity ( Martens et al, 2012 ; Kao et al, 2017 ; Logan et al, 2021 ; Mohan et al, 2021 ; Simon et al, 2022 ). Thus, our stem cell model revealed several genes and pathways that are also altered in primary tauopathy patients.…”
Section: Discussionmentioning
confidence: 99%
“…Progranulin (PGRN, officially known as GRN) is a soluble glycoprotein that is proteolytically processed into 6 kDa granulins within endo-lysosomes by cathepsins ( Table 1 ) ( Toh et al, 2011 ; Zhou et al, 2017 ; Mohan et al, 2021 ). Although its function is not well defined, GRN is known to localize within lysosomes and extracellularly, and has been linked to cell migration, inflammation, and processes related to cancer progression ( Table 1 ) ( Zhou et al, 1993 ; Tian et al, 2016 ; Daya et al, 2018 ; Paushter et al, 2018 ; Voshtani et al, 2019 ).…”
Section: The Roles Of Cln Genes and Proteins In Au...mentioning
confidence: 99%